Cloning and characterization of Plasmodium vivax serine hydroxymethyltransferase. - Leartsakulpanich, U; Kongkasuriyachai, D; Imwong, M; Chotivanich, K; Yuthavong, Y (2008)
Serine hydroxymethyltransferase (SHMT), which catalyzes the reversible reaction of serine and tetrahydrofolate to glycine and methylenetetrahydrofolate, is one of the three enzymes in dTMP synthesis pathway that is highly active during cell division and has been proposed as a potential chemotherapeutic target in infectious diseases and cancer. This is the first study to describe nucleotide and amino acid sequences of SHMT from the malaria parasite Plasmodium vivax. Sequencing of 12 P. vivax isolates revealed limited polymorphisms in 3 noncoding regions. Its biological function is also reported.